Non-Hodgkin’s Lymphoma in Northern India: An Analysis of Clinical Features of 241 Cases - Sandhu, Devinder Singh; Sharma, Atul; Kumar, Lalit (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Geographic variations with regard to incidence, clinical presentation, and histological subtypes are known to occur in several cancers. This study was aimed to see if similar differences existed in non-Hodgkin's lymphoma (NHL) also during pre-immunohistochemical era. Materials and Methods: Cases of NHL seen at Institute Rotary Cancer Hospital, All India Institute of Medical Sciences, New Delhi from January 1997 to December 2000, were analyzed for baseline clinical features and histology. Results: Total cases: 241, median age: 47 years (range 2–84 years), male-female ratio: 2.2:1, primary extranodal NHL: 44.2%, the most common histological subtype: Diffuse large cell (6.2% of the cases). Conclusion: Our patients presented at younger median age, had more male to female ratio, had diffuse large cell histology as the most common histological subtype.
Keywords: Extranodal non-Hodgkin's lymphoma; non-Hodgkin's lymphoma; Northern India